2012
DOI: 10.1155/2012/856759
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 is the Leading Cause of Genital Herpes in New Brunswick

Abstract: INTRoDuCTIoN:Little is known about the role of herpes simplex virus (HSV) type 1 (HSV1) in the epidemiology of genital herpes in Canada. Data on herpes viral cultures for two consecutive years obtained from L'Hôpital Dr GL Dumont, which performs all the viral culture testing in New Brunswick, were reviewed. It was hypothesized that HSV1 was the main cause of genital herpes in New Brunswick. MeTHoDs: Samples of genital origin sent to the laboratory for HSV culture testing between July 2006 and June 2008 were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Present statistics put the seroprevalence of HSV-1 at over 60% of the adult population of the United States and that of HSV-2 at 20% ( 5 ). Although historically, HSV-1 was the main causative agent of oral lesions and HSV-2 of genital lesions, an increasing percentage of genital herpesvirus cases are due to HSV-1 infection ( 6 8 ). This shift creates a need to understand the mechanisms of diversity and selection of HSV-1 and -2 during human infection and to understand the selective forces and bottlenecks that influence coinfection and viral adaptation ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Present statistics put the seroprevalence of HSV-1 at over 60% of the adult population of the United States and that of HSV-2 at 20% ( 5 ). Although historically, HSV-1 was the main causative agent of oral lesions and HSV-2 of genital lesions, an increasing percentage of genital herpesvirus cases are due to HSV-1 infection ( 6 8 ). This shift creates a need to understand the mechanisms of diversity and selection of HSV-1 and -2 during human infection and to understand the selective forces and bottlenecks that influence coinfection and viral adaptation ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both types of HSV could be responsible for genital herpes. [1,5]. HSV plays a role as a co-factor in the acquisition of HPV infection [1].…”
Section: Discussionmentioning
confidence: 99%
“…The tropism of the virus seems to have changed. Clinical reports indicate an increasing number of genital herpes infections caused by HSV -1, although HSV -2 dominates as a causative agent [4,5]. The viruses infect humans of all ages and cause lasting and recurrent infections throughout life [4].…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 Although HSV-1 was most prevalent in pre-term delivery (33%) cases in this study, there were no statistical differences between other groups due to the small number of samples. Garceau, et al 26 reported that HSV-1 was found in 62.6% of genital herpes patients and was a common cause of genital herpes in New Brunswick in Canada. Therefore, HSV-1 infection still warrants detection during pregnancy.…”
Section: Discussionmentioning
confidence: 99%